Hijab & the republic : uncovering the French headscarf debate - Winter, Bronwyn, 1955- (Syracuse, N.Y. : Syracuse University Press, 2008)
A riveting account of the controversial 2004 French law to ban Islamic headscarves and other religious signs from public schools.
Introduction : why France? -- pt. 1. Contextualizing the debate: A very modern tradition : background to the "new veiling" ; The "cornerstone of the republic" : secularism and the regulation of religion ; French Muslims : between "integration" and "Muslimism" -- pt. 2. A fifteen-year saga: 1989 : three little girls and a great big "psychodrama" ; 1990-1995 : from psychodrama to saga ; 1995-2004 and beyond : how ostentatiousness became conspicuous -- pt. 3. Feminists caught in the contradictions: The politics of hijabization ; Co-optations and instrumentalizations ; Feminist confusions and confrontations -- Conclusion : French lessons for the West? -- Appendix : Chronology.
Includes bibliographical references (pages 357-383) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 050
Keywords: Hijab (Islamic clothing) -- France; Veils -- Social aspects -- France; Muslim women -- Clothing -- France; Clothing and dress -- Religious aspects -- Islam; Clothing and dress -- Political aspects -- France; Islam and secularism -- France; France -- Race relations; HEALTH & FITNESS -- Beauty & Grooming; HISTORY -- Europe -- France; Hoofdbedekking; Islam; Vrouwen; Politieke aspecten; Frankrijk; Electronic books